Thermoelectric refrigerator for sleeping car compartments - Filin, S.O.; Filina-Dawidowicz, L.S.; Wiśniewski , V. (Journal of Thermoelectricity, 2022)
In this work, a thermoelectric refrigerator was designed, the cooling unit of which is built into a corner cabinet in the sleeping compartment of a PKP Intercity model 308A car. The design of the cooling unit provides for several execution options. The modernization of the car is carried out by PESA Bydgoszcz. The refrigerator has an innovative two-level power supply system, which allows reducing energy consumption. The refrigerator cabinet is divided into two chambers "serving" two adjacent compartments. The thermoelectric unit of the refrigerator cools both chambers simultaneously. The application of the invention allows increasing the comfort level of travelers.